Impact of abusive supervision, perceived injustice and cultural values on counterproductive work behaviours of nurses in public healthcare in Malaysia - Low, Yoke May (2016)
Counterproductive Work Behaviours has captured the attention of organizational researchers due to its pervasiveness in the workplace. Previous research has indicated that patient satisfaction is one of the priorities in any healthcare organization. Hence, it is of great importance to mitigate counterproductive work behaviours among nurses in order to assist patrons in achieving anticipated outcomes and satisfaction. Yet, there is a gap in literature whereby the contingencies affecting nurses’ perception of injustice and decision in engaging CWB subjected to abusive supervision have not been explored extensively. This study fills the gap by examining the relationship between abusive supervision, nurses’ perception of injustice, individual differences (collectivism value orientation, power distance orientation and locus of control) and CWB using a sample of 337 nurses in six public hospitals in Klang Valley, Malaysia. Data was collected through questionnaire survey using drop and pick method. Descriptive and inferential statistical analyses were conducted to respond to the four research questions and research objectives of the study. Furthermore, a total of seven hypotheses were tested in this study using partial least square structural equation modeling (PLS-SEM). Results of the analyses indicate that there is a significant relationship between (i) abusive supervision and nurses’ perception of injustice, (ii) abusive supervision and counterproductive work behaviours, and (iii) nurses’ perception of injustice and counterproductive work behaviours. Moreover, nurses’ perception of injustice is found to mediate the relationship between abusive supervision and counterproductive work behaviours. Furthermore, support is also found for the moderating effect of power distance orientation and locus of control on the relationship between abusive supervision and nurses’ perception of injustice, and nurses’ perception of injustice and counterproductive work behaviours respectively. However, the moderating effect of collectivism value orientation is found to be insignificant. The findings of this study provide a theoretical basis and empirical evidences of individual differences (power distance orientation and locus of control) in mitigating counterproductive work behaviours among nurses. In terms of practise, the findings can assist nurse manager and hospital management in nurses’ selection and providing suitable training programs for the nurses. This research applied a crosssectional study design and self-report measures but still presented significant implications for existing and future theoretical models of abusive supervision and counterproductive work behaviours.